Postural control and functional balance in individuals with diabetic peripheral neuropathy - Ana Claudia de Souza Fortaleza; Eliane Ferrari Chagas; Dalva Minonroze Albuquerque Ferreira; Alessandra Madia Mantovani; José Ângelo Barela; Eduardo Federighi Baisi Chagas; Cristina Elena Prado Teles Fregonesi (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
Diabetic Peripheral Neuropathy (DPN) brings on reduced somatosensation, which can lead to changes in postural control. The objective of this study was to evaluate postural control in a standing position and in different conditions, as well as functional balance in individuals with DPN, make the correlation between the results obtained from the postural control assessment with the values from the functional balance test and compare the results obtained in the neuropathy group with those of the control group, checking for possible differences between the evaluation conditions of both groups. The study included 13 women with DPN (NG) and 17 non-diabetic women (CG). Postural control assessment was performed by kinemetry in the following conditions: eyes opened (EO), eyes closed (EC), and semi-tandem (ST). The data was processed in MATLAB and the following variables were generated: mean amplitude of oscillation (MAO) in the anterior-posterior (AP) and medial-lateral (ML) direction; and average speed of oscillation (ASO) in AP and ML direction. Functional balance was assessed by the Timed Up and Go Test. There was significant difference between the groups (p≤0.005) in MAO-AP EO and EC, MAO-ML EC and ST, and ASO-ML ST. There were differences between the conditions EO and ST (p≤0.005) and EC and ST (p≤0.005) for the variables MAO-ML and ASO-ML with greater damage to the NG, which also had a lower functional balance (p=0.001). ML instability was positively correlated with functional imbalance. The results show a change in the postural control system in the DPN, which could lead these individuals to a higher risk for falls and functional impairment.